Nagios Core Administration Cookbook. - Ryder, Tom (Packt Pub., 2013)
This book is written in Cookbook style, beginning with recipes based on basic structure which gradually progresses towards using Nagios Core as a monitoring framework. This book is for System Administrators who are looking for recipes to help them deal with advanced network monitoring issues with Nagios Core.